Analysis of the Influence of Human Resources Development Programs, Transformational Leadership, and Compensation Policies on Employee Retention at Perhutani Public Company in Jakarta, Indonesia - Sri Suryani; Syamsulbahri Syamsulbahri (West Science Journal Economic and Entrepreneurship, 2024)
This research delves into the intricate dynamics of employee retention within Perhutani General Company, Jakarta, Indonesia, focusing on the impact of Human Resource Development Programs (HRDP), Transformational Leadership (TL), and Compensation Policies (CP). A quantitative approach, employing a sample of 250 employees, was utilized to assess the relationships among these variables. The study's methodology involved a robust measurement model assessment, hypothesis testing, and structural model analysis. The results underscore the significant positive influence of HRDP (path coefficient = 0.626, p < 0.001), TL (path coefficient = 0.442, p = 0.002), and CP (path coefficient = 0.348, p = 0.003) on Employee Retention (ER). The measurement model validation ensures the reliability and validity of the constructs. The R-Square of 0.602 and Adjusted R-Square of 0.592 indicate a satisfactory fit of the model. Practical implications suggest strategic interventions tailored to the unique contributions of each factor. While the study provides valuable insights, future research should consider longitudinal approaches and diverse organizational contexts to enrich the generalizability of findings.